CHANGES IN THE SOCIETY ENVIRONMENT ON THE EFFECTIVENESS OF COMPUTER NETWORK DISTRIBUTION - Aldy Agustian; Ardiansyah; Perianus Lombu; Kiki Wulandari; Muhammad Amin (RADJA PUBLIKA, 2025)
The proliferation of computer networks has significantly impacted various aspects of social life. This study aims to identify and analyze the social changes resulting from the integration of computer networks into everyday life. Using a mixed-method research design, data were collected through a survey involving 300 respondents and in-depth interviews with 40 informants. The results indicate that computer networks increase the frequency of communication with family and friends (78%), facilitate access to information and education (70%), and enable more flexible work and education patterns, with 60% of respondents working from home and 50% participating in online learning. Furthermore, computer networks also increase economic opportunities such as online jobs and e-commerce businesses (68%). However, the study also reveals a digital divide, particularly in rural areas (40%), indicating the need for further efforts to ensure the equitable distribution of the benefits of technology. This study provides in-depth insights into the impact of computer networks on social transformation and can be used as a reference for policymakers, educators, and information technology professionals in developing effective strategies to leverage this technology for social and economic progress.